1997
DOI: 10.1002/(sici)1097-0231(199703)11:5<443::aid-rcm897>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Proton Affinities of Eight Matrices Used for Matrix-assisted Laser Desorption/Ionization

Abstract: Since its introduction by Karas and co-workers in 1987, matrix-assisted laser desorption/ionization (MALDI) has rapidly become a vital tool in the study of large molecules.1-10 The mechanism of ionization during MALDI is still poorly understood, and no adequate quantitative model for the complete process exists. The MALDI technique involves both laser ablation and ionization of the matrix/analyte mixture. Spectra are dominated by matrix photoproducts, protonated molecules, and adduct ions. Several groups have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…From the calculations, the CN is the most stable protonation site followed by the ␣-C and the OH (15 kcal/ mol and 39 kcal/mol higher than the value found for CN). The calculated values agree with those found previously using the gas-phase bracketing method in combination with Fourier transform ion cyclotron resonance (FTICR) mass spectrometry [13] and using the kinetic method [12]. Experimental PA values for DHB are in the range 197 Ϭ 204 kcal/mol and for 4HCCA in the range 183 Ϭ 223 kcal/mol.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…From the calculations, the CN is the most stable protonation site followed by the ␣-C and the OH (15 kcal/ mol and 39 kcal/mol higher than the value found for CN). The calculated values agree with those found previously using the gas-phase bracketing method in combination with Fourier transform ion cyclotron resonance (FTICR) mass spectrometry [13] and using the kinetic method [12]. Experimental PA values for DHB are in the range 197 Ϭ 204 kcal/mol and for 4HCCA in the range 183 Ϭ 223 kcal/mol.…”
Section: Resultssupporting
confidence: 86%
“…Many analytes, especially peptides and proteins, are detected predominantly in protonated form. Reactions between peptides/proteins in the gas phase were reported to have proton affinities (PAs) greater than 215 kcal/mol [10], whereas PAs of the most common matrices are between 200 and 215 kcal/mol [11][12][13], making the proton transfer between protonated matrix and neutral analyte favorable. Strong evidence for proton transfer reactions between protonated matrix and analyte was recently reported using mixtures of conventional matrices and various amino acids varying in gas phase basicity [6].…”
mentioning
confidence: 99%
“…Recent bracketing experiments have shown markedly lower PA for CHCA (183 ( 2 kcal/mol) than for SA (204 ( 4 kcal/mol). 28 One can argue that proton transfer from the ground state of the protonated CHCA species to Gly n occurs more readily than from protonated SA due to the ∼21 kcal/mol advantage in the PA balance.…”
Section: Resultsmentioning
confidence: 99%
“…Limited theoretical and experimental studies of the gas phase properties of MALDI matrices have been reported in the literature. These studies have focused on determining the gas phase proton affinities [43][44][45][46], basicities/acidities [47][48][49][50], and ionization energies of MALDI matrices [43]. Very few studies have reported cation affinities [51][52][53][54][55] of MALDI matrices.…”
Section: Introductionmentioning
confidence: 99%